1994
DOI: 10.1073/pnas.91.11.5119
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of CspA, the major cold shock protein of Escherichia coli.

Abstract: The major cold shock protein of Eschenchia coli, CspA, produced upon a rapid downshift in growth temperature, Is involved in the transcriptional regulation of at least two genes. The protein shares high homology with the nucleic acid-binding do of the Y-box factors, a family of eukaryotic proteins involved in nscriptional and trandational regulation. The crystal structure of CspA has been determined at 2-A resolution and refined to R = 0.187. CspA Is composed of five antiparallel -strands forming a osed five-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
293
1
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(302 citation statements)
references
References 30 publications
5
293
1
3
Order By: Relevance
“…IF1 displays a striking structural resemblance to the major cold shock protein CspA [34,35]. It has also been shown that heterologous expression of IF1 from E. coli in a Bacillus subtilis cspB/cspC double deletion strain complemented the loss of the cold shock induced protein CspB in B. subtilis (the homolog of CspA in E. coli) [36].…”
Section: Discussionmentioning
confidence: 98%
“…IF1 displays a striking structural resemblance to the major cold shock protein CspA [34,35]. It has also been shown that heterologous expression of IF1 from E. coli in a Bacillus subtilis cspB/cspC double deletion strain complemented the loss of the cold shock induced protein CspB in B. subtilis (the homolog of CspA in E. coli) [36].…”
Section: Discussionmentioning
confidence: 98%
“…A similar sequence motif (coldshock domain) has been found in eukaryotic DNA and RNA binding proteins called Y-box proteins (Wolffe et al 1992). The three-dimensional structure of CspA has been determined by NMR spectroscopy (Newkirk et al 1994) as well as X-ray crystallography (Schindelin et al 1994). It consists of five antiparallel -sheet structures, and seven surface aromatic residues were shown to interact with single-stranded DNA.…”
Section: Introductionmentioning
confidence: 99%
“…CspA, the most prominent of the nine-member E. coli CSP family, accumulates up to 10% of total proteins during cold stress (Jiang et al, 1997). The three-dimensional structure of E. coli CspA forms a five-stranded ␤-barrel structure (Newkirk et al, 1994;Schindelin et al, 1994) that contains two consensus RNA-binding motifs (RNP1 and RNP2), which facilitate nucleic acid recognition/binding (Schroder et al, 1995). CspA has been hypothesized to prevent RNA secondary structure formation (Jiang et al, 1997), thereby enhancing translation at low temperature.…”
mentioning
confidence: 99%